Bird Assemblages in Anthropogenic Habitats: Identifying a Suitability Gradient for Native Species in the Atlantic Forest - Zurita, Gustavo Andres (2012)
Traditional approaches to the study of species persistence in fragmented landscapes generally consider a binary classification of habitat being suitable or unsuitable; however, the range of human-modified habitats within a region may offer a gradient of habitat suitability (or conservation value) for species. We identified such a gradient by comparing bird assemblages among contrasting land uses (pine plantations of different age, annual crops, clear cuts and cattle pastures) in the Upper Parana Atlantic forest. Bird assemblages and vegetation structure were characterized in an extensive area of 4400 km 2 in Argentina and Paraguay during the breeding seasons of 2005-2010. Similarity of bird assemblages between anthropogenic habitats and the native forest and the proportion of forest species increased with vegetation vertical structure, while the proportion of open-area species decreased. As a consequence, mature tree plantations were the most suitable habitats for forest species and were mainly used by frugivores and bark insectivores. In contrast, open habitats were the least suitable habitat for forest species and were used primarily by insectivores. Human-created habitats that are structurally complex can be used by a subset of forest species, and may improve functional connectivity and mitigate edge effects. The conservation of large tracks of native forests, however, is critical for the long-term persistence of the entire bird assemblage, especially for native forest dependent species.